Investigating teachers' post-pandemic management of mathematics content coverage in Grade 3 - Damaske, Inge Gerda (Rhodes University, Faculty of Education, Department of Primary and Early Childhood Education)
This study investigated how teachers managed and continue to manage mathematics content coverage in Grade 3 during the COVID-19 pandemic and now post the pandemic. In particular my study sought to understand technologies that teachers may have drawn on during the pandemic in support of curriculum coverage and those that they continue to use. In addition, the study began with a detailed documentary analysis of all available documentation provided to schools and teachers about the management of teaching and curriculum coverage during the pandemic as this provides understanding of the policy and guidelines context in which teachers were working. Thus, in this research I investigated the research questions: i) How have teachers managed the stipulated curriculum coverage in Grade 3 mathematics during the pandemic? and ii) How are teachers continuing to manage this post the pandemic. This included identifying how much and what type of support teachers were given from various stakeholders in the primary education system. Here the levels of support from school principals, governing bodies and more importantly the Department of Basic Education were analysed. This research, situated within an interpretative paradigm, was guided by the sociocultural theory inherent in the concerns-based adoption model. The levels of use within the concerns-based adoption model were adapted to suit the South African context of the study. Participants of the study were 18 teachers from different quintile schools within the Tshwane South District. Key findings included that the Department of Basic Education (DBE) provided a range of documents aimed at adjusting content coverage in response to the altered school calendar during the pandemic. Notable adjustments, particularly in the Annual Teaching Plans (ATPs) of 2020, revealed discrepancies in allocated school days and modifications in content areas such as numbers, operations, geometry, measurement, and data handling. The reduction in the number range and fluctuations in measurement components were observed. Despite the provision of guidelines, the study notes challenges in maintaining continuity and optimal learning, with indications of non-compliance with provided ATPs. The study further found that teachers in different quintile schools adopted diverse strategies for mathematics content coverage during the pandemic. Quintile 5 schools, often well-resourced, reported effective remote teaching using tools like PowerPoint and MS Teams. In contrast, teachers in quintiles 3 and 4, more impacted by school closures, employed varied methods, including extra lessons. Surprisingly, teachers in well-resourced private schools reported gaps in learners' mathematical knowledge, emphasizing the flexibility they have in curriculum coverage. Technology played a pivotal role in facilitating remote teaching during the pandemic, with tools like WhatsApp, MS Teams, and Zoom being widely used, where available. The study underscored the impact of technology on curriculum coverage, especially in well-resourced schools. Grade 3 teachers expressed challenges in meeting unrealistic expectations for curriculum coverage, citing gaps in learners' understanding. The study highlighted a discrepancy between the resources provided by the DBE and the actual needs on the ground, signalling a need for policymakers to become more understanding to the situations in schools. The lack of support from the DBE prompted teachers to become flexible, adapting teaching strategies and supporting each other to navigate the challenges posed by the pandemic. The study concludes by noting the evolving mindset of teachers, transitioning through different levels of Concerns-Based Adoption Model (CBAM), ultimately showcasing their resilience and adaptability in managing curriculum coverage with the available resources.
Keywords: COVID-19 Pandemic, 2020- Influence; Mathematics-- Study and teaching (Elementary) -- South Africa City of Tshwane Metropolitan Municipality; Elementary school teachers -- South Africa City of Tshwane Metropolitan Municipality; Educational technology; Curriculum planning